Sans analysis on CTAB (Cetyltrimethyl ammonium bromide micellar solution) - Ullah, A.K.M. Shafiq; Kamal, Imtiaz (BRAC University, 2010)
The CTAB (Cetyltrimethyl Bromide) micellar solutions are studied by SANS measurement for different concentrations and at different temperatures with the additives of NaSal. The concentrations are 0.1M, 0.2M and 0.4M in D2O system. The temperatures are 30C, 40C and 60C for the solution 0.1MCTAB+0.03MNaSal. The data are analyzed by Hayter and Penfold type analysis and it gives the information of different parameters such as aggregation numbers, charge, minor and major axes and the inter particle separations at different concentrations and temperatures of the micelles.